2017
DOI: 10.1128/aac.02257-16
|View full text |Cite
|
Sign up to set email alerts
|

Results from a Patient-Based Health Education Intervention in Reducing Antibiotic Use for Acute Upper Respiratory Tract Infections in the Private Sector Primary Care Setting in Singapore

Abstract: We investigated the efficacy of patient-targeted education in reducing antibiotic prescriptions for upper respiratory tract infections (URTIs) among adults in the private primary care setting in Singapore. Our randomized controlled trial enrolled patients aged 21 years and above presenting at general practitioner (GP) clinics with URTI symptoms for 7 days or less. Intervention arm patients were verbally educated via pamphlets about the etiology of URTIs, the role of antibiotics in treating URTIs, and the conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
58
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(58 citation statements)
references
References 33 publications
(38 reference statements)
0
58
0
Order By: Relevance
“…However, some children can develop pneumonia, which requires hospitalization and specialized treatment 198 . Despite URTIs generally being minor illnesses, they result in an appreciable number of medical consultations globally 87,[199][200][201][202][203] . The number of healthcare consultations combined with parental and patient pressure increases antibiotic use for URTIs including LMICs thereby increasing AMR rates 88,153,200,[204][205][206][207][208][209] .…”
Section: Aetiology Of Urtis and Symptomsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some children can develop pneumonia, which requires hospitalization and specialized treatment 198 . Despite URTIs generally being minor illnesses, they result in an appreciable number of medical consultations globally 87,[199][200][201][202][203] . The number of healthcare consultations combined with parental and patient pressure increases antibiotic use for URTIs including LMICs thereby increasing AMR rates 88,153,200,[204][205][206][207][208][209] .…”
Section: Aetiology Of Urtis and Symptomsmentioning
confidence: 99%
“…Despite URTIs generally being minor illnesses, they result in an appreciable number of medical consultations globally 87,[199][200][201][202][203] . The number of healthcare consultations combined with parental and patient pressure increases antibiotic use for URTIs including LMICs thereby increasing AMR rates 88,153,200,[204][205][206][207][208][209] . Patients or parents who are concerned about their or their child's respiratory illness are likely to seek treatment, and want an antibiotic, especially if they perceive the illness as severe 21,209,210 .…”
Section: Aetiology Of Urtis and Symptomsmentioning
confidence: 99%
“…As mentioned before, the unnecessary use of antibiotics to treat upper respiratory infections leads to consequences like increased drug-resistance, increased health care costs, and increased incidences of adverse effects (O'Sullivan, Harvey, Glasziou, & McCullough, 2016;Lee et al, 2017). Uncomplicated URIs result in 25 million visits to primary care providers across the United States each year (Zoorob, Sidani, Fremont, &Kihlberg, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…An evidence-based review of numerous research studies aimed at reducing antibiotic prescriptions for upper respiratory infections was conducted using PubMed, Google Scholar, and various online resources (e.g., CDC, UpToDate). From these resources, five studies were found to show that printed information given to patients presenting with upper respiratory infections would result in reduced prescription rates for antibiotics (Lee et al, 2017;Wei et al, 2017;Gonzales et al, 2013;Agnew, Taaffe, Darker, O'Shea, & Clarke,2013;Meeker et al, 2014). The use of printed information would come in various forms, including leaflets, brochures, pamphlets, and a poster-size education/commitment letter (Lee et al, 2017;Wei et al, 2017;Gonzales et al, 2013;Agnew et al,2013;Meeker et al, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation